SEISMIC FLOW OF THE LITHOSPHERE BENEATH KAMCHATKA - Vostrikov G.A. (My University, 1996)
This study is concerned with spatial variations in strain and stress rates and in viscosity, these being macroscopic effective parameters of seismic flow in the crust and upper mantle (down to 60 km depth) beneath Kamchatka. The quantities characterizing these macroscopic parameters are estimated by interpreting relations between the frequency of earthquakes and their energy classes in terms of seismic flow. A relationship between the total tectonic flow and the flow due to earthquake slip is discussed. An interference between two zones has been discovered: a strong homogeneous block dipping at ~35° under the continent and a subhorizontal zone of low viscosity within the crust.